Nutritional composition and action mechanism of Channa striata meat in wound healing: A systematic review - Hapsari, Riani; Tjandrawinata, Raymond (Narra J, 2025)
Wound healing is a complex biological process requiring adequate nutritional support, particularly proteins, amino acids, fatty acids, and essential minerals. Snakehead fish (Channa striata) has been traditionally consumed in Southeast Asia to accelerate recovery after surgery and childbirth. Emerging evidence suggests that its nutritional composition plays a pivotal role in tissue repair. The aim of this systematic review was to consolidate evidence on the nutritional composition of C. striata and elucidate its mechanisms of action in wound healing based on preclinical and clinical studies. A systematic search was conducted across PubMed, ScienceDirect, ProQuest, and Google Scholar for studies published between 2000 and 2023, following PRISMA 2020 guidelines. Eligible studies included biochemical analyses, in vitro and in vivo preclinical studies, and clinical trials assessing the wound-healing effects of C. striata. Data extraction covered nutrient composition, study design, wound-healing parameters, and mechanistic pathways. Out of 2898 identified studies, 22 of them met the inclusion criteria: ten biochemical composition studies, nine preclinical investigations, and four clinical trials. C. striata extract demonstrated high levels of albumin (0.76–10.73 g/100 g), essential and non-essential amino acids (notably glutamic acid, arginine, and glycine), fatty acids (palmitic, arachidonic, linoleic), and minerals such as zinc and copper. Preclinical models consistently showed enhanced fibroblast proliferation, epithelialization, tensile strength, and collagen deposition. Clinical studies in post-cesarean patients reported significant improvements in wound healing scores, uterine involution, pain reduction, and biomarker modulation (VEGF, IL-6, MMP-9). In conclusion, C. striata exhibits promising wound-healing potential attributable to its rich nutrient profile and multi-pathway mechanisms involving collagen synthesis, angiogenesis, and immunomodulation. However, the limited number of clinical trials underscores the need for larger, well-designed studies to confirm its translational efficacy in human wound care.